2012
DOI: 10.1371/journal.pone.0031827
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a Is Strongly Expressed at the Leading Edge in Non-Melanoma Skin Cancer, Forming Active Gradients, while Canonical Wnt Signalling Is Repressed

Abstract: Wnt5a is one of the so-called non-canonical Wnt ligands which do not act through β-catenin. In normal development, Wnt5a is secreted and directs the migration of target cells along concentration gradients. The effect of Wnt5a on target cells is regulated by many factors, including the expression level of inhibitors and receptors. Dysregulated Wnt5a signalling facilitates invasion of multiple tumor types into adjacent tissue. However, the expression and distribution of Wnt5a in cutaneous squamous cell carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
56
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 47 publications
4
56
1
Order By: Relevance
“…Topol et al (39) subsequently uncovered that Wnt5a inhibited canonical Wnt/β-catenin signaling by modulating β-catenin degradation via a GSK3-independent mechanism. Similar inhibition mechanisms of Wnt5a have been identified in hematopoietic stem cells (40), hepatocyte proliferation (41), dermal papilla cells and non-melanoma skin cancer (42). Therefore, Wnt5a functions as an antagonist of the canonical Wnt/β-catenin pathway, and may account for the unusual results in the present study concerning Wnt/β-catenin signaling in gliomas.…”
Section: Discussionsupporting
confidence: 84%
“…Topol et al (39) subsequently uncovered that Wnt5a inhibited canonical Wnt/β-catenin signaling by modulating β-catenin degradation via a GSK3-independent mechanism. Similar inhibition mechanisms of Wnt5a have been identified in hematopoietic stem cells (40), hepatocyte proliferation (41), dermal papilla cells and non-melanoma skin cancer (42). Therefore, Wnt5a functions as an antagonist of the canonical Wnt/β-catenin pathway, and may account for the unusual results in the present study concerning Wnt/β-catenin signaling in gliomas.…”
Section: Discussionsupporting
confidence: 84%
“…More microarrays demonstrated that Wnt5a was increased in psoriatic plaques of patients, indicating that the noncanonical Wnt signaling pathway might be activated in psoriasis (8,43). Despite the controversial findings of whether the canonical or noncanonical Wnt pathway was activated in psoriasis (9,10,42), all of the studies pointed out that the expression of inhibitory factors related to Wnt signaling, such as SFRP, Dkk, and WIF, were reduced to some extent in psoriasis (8,10). In the current study, we found that the expression of SFRP4, a negative modulator of Wnt signaling (45), was decreased in lesional skin of psoriasis mouse models and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Geneticassociated studies identified dozens of psoriasis-associated genes and the signaling pathways (3), such as the IL-23/Th17 axis (4), the NF-kB signaling pathway (5), and the epidermal differentiation complex (6,7). Recently, several independent array-based studies revealed that Wnt signaling was altered in psoriatic skin compared with normal skin (8)(9)(10), suggesting that this pathway might be involved in psoriasis pathogenesis.…”
mentioning
confidence: 99%
“…WNT/β-catenin-independent signaling also regulates cSCC cells, where WNT5A leads to chemotactic migration at the leading edge of human cSCC tumours (Pourreyron, et al 2012). Furthermore, epigenetic profiling of metastatic cSCC compared to non-metastatic tumours, identified the FrzB gene, which encodes for the secreted WNT inhibitor, SFRP3, as having the most hypermethylated promoter in human cSCC, suggesting that loss of SFRP3 expression and subsequent WNT activation is a critical step in the development of metastatic tumours (Darr, et al 2015).…”
Section: Wnt Signaling In Csccmentioning
confidence: 99%
“…WNT/β-catenin-independent signaling also promotes cSCC progression (Pourreyron, et al 2012), suggesting that intervention at this arm of the WNT network also has therapeutic potential, albeit there are few inhibitors currently targeted to this pathway. However a WNT5A-derived hexapeptide, termed Box5, 12 developed to inhibit WNT/Ca 2+ signaling in melanoma (Jenei, et al 2009), has recently been shown to antagonise WNT5A/Ca 2+ signaling in HNSCC (Prgomet, et al 2015).…”
Section: Wnt Signaling In Csccmentioning
confidence: 99%